LAG-3 expression in microglia regulated by IFN-γ/STAT1 pathway and metalloproteases - Morisaki, Yuta; Ohshima, Motoki; Suzuki, Hikaru; Misawa, Hidemi (Frontiers in Cellular Neuroscience, 2023)
Microglia are resident innate immune cells in the central nervous system (CNS) and play important roles in the development of CNS homeostasis. Excessive activation and neurotoxicity of microglia are observed in several CNS disorders, but the mechanisms regulating their activation remain unclear. Immune checkpoint molecules are expressed on activated immune cells and regulate their activation in peripheral immunity. However, the expression mechanism of immune checkpoint molecules in activated microglia is still unknown. Here, we analyzed the expression of immune checkpoint molecules in activated microglia using the mouse microglial cell line BV2 and primary cultured microglia. The expression of lymphocyte activation gene-3 (LAG-3), a type of immune checkpoint molecule, was increased in microglia activated by IFN-γ. IFN-γ-induced LAG-3 expression in microglia was suppressed by transfection of siRNA targeting STAT1. LAG-3 has two forms, membrane and soluble, and both forms were upregulated in microglia activated by IFN-γ. The production of soluble LAG-3 was suppressed by treatment with inhibitors of metalloproteinases such as ADAM10 and ADAM17. IFN-γ administration into cisterna magna of mice increased LAG-3 expression in spinal microglia. Furthermore, LAG-3 knockdown in microglia promoted nitric oxide (NO) production by IFN-γ. Our results demonstrate that LAG-3 expression in microglia is induced by the IFN-γ-STAT1 pathway and soluble LAG-3 production is regulated via cleavage of membranous LAG-3 by metalloproteinases including ADAM10 and ADAM17.